Principles of Effective Online Learning: Developing a Curriculum for Virtual Classroom - David Tjahjana (STAI Hubbulwathan Duri, 2023)
Colleges and universities of all sizes are expanding into online education in response to rising demand from students and academics. Using the ideas of learner-centeredness, constructivism, and contextual learning, this article explores the five cornerstones of online learning. The capacity to (a) cultivate a sense of belonging and community, (b) integrate active learning, (c) leverage learner agency, (d) embrace mastery learning, and (e) adapt one's educational experience are all cornerstones. In this article, the authors evaluate 40 studies published in the last five years to draw conclusions on the fundamentals of efficient online education. This paper presents an analysis of the concerns and obstacles encountered during the development of a curriculum for virtual classrooms. The identified issues are thoroughly examined and potential solutions are proposed and debated.